2016
DOI: 10.1016/j.neuron.2016.09.057
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch Receptive Fields in Mouse Visual Cortex

Abstract: In primary visual cortex, a subset of neurons responds when a particular stimulus is encountered in a certain location in visual space. This activity can be modeled using a visual receptive field. In addition to visually driven activity, there are neurons in visual cortex that integrate visual and motor-related input to signal a mismatch between actual and predicted visual flow. Here we show that these mismatch neurons have receptive fields and signal a local mismatch between actual and predicted visual flow i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
190
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 157 publications
(205 citation statements)
references
References 33 publications
15
190
0
Order By: Relevance
“…Hence, the amplitude of error responses will reflect both differences in top-down predictions and differences in predicted precision. Indeed, as mentioned above, many studies have reported that stimulus-evoked responses are inversely proportional to the degree to which the stimulus was expected, 47,75,76,[83][84][85]98 although this effect is not universally observed. 79,82 In PP, stimulus salience and attention are considered emergent properties of this precisionweighting mechanism.…”
Section: Expectation Suppressionmentioning
confidence: 97%
See 3 more Smart Citations
“…Hence, the amplitude of error responses will reflect both differences in top-down predictions and differences in predicted precision. Indeed, as mentioned above, many studies have reported that stimulus-evoked responses are inversely proportional to the degree to which the stimulus was expected, 47,75,76,[83][84][85]98 although this effect is not universally observed. 79,82 In PP, stimulus salience and attention are considered emergent properties of this precisionweighting mechanism.…”
Section: Expectation Suppressionmentioning
confidence: 97%
“…Acquiring recordings from distinct cortical layers, whether directly or indirectly, may be essential to overcoming many of these obstacles and adding to what is currently a limited evidence base supporting the existence of functionally distinct subpopulations (e.g., Refs. 47 and 98).…”
Section: Hypothesis 3: Each Level Of the Cortical Hierarchy Houses Twmentioning
confidence: 98%
See 2 more Smart Citations
“…Another idea is that layer 2/3 (L2/3) neurons use a difference between bottom-up visual input and a top-48 down prediction to compute visuomotor prediction errors (Keller and Mrsic-Flogel, 2018). This was based 49 on the finding that a subset of L2/3 neurons strongly respond to a sudden mismatch between visual flow 50 feedback and locomotion speed (Keller et al, 2012;Zmarz and Keller, 2016). This last interpretation is at 51 the core of the framework of predictive processing.…”
Section: Introduction 20mentioning
confidence: 99%